2013
DOI: 10.1371/journal.pone.0068798
|View full text |Cite
|
Sign up to set email alerts
|

Indications of Clinical and Genetic Predictors for Aromatase Inhibitors Related Musculoskeletal Adverse Events in Chinese Han Women with Breast Cancer

Abstract: BackgroundWomen with breast cancer treated with aromatase inhibitors (AIs) may experience musculoskeletal symptoms that lead to discontinuation of effective therapy. The purpose of the current study is to evaluate the clinical and genetic predictors for AIs-related musculoskeletal adverse events(MS-AEs).Methodology and Principal FindingsWe recruited 436 postmenopausal Chinese Han women receiving adjuvant AIs therapy for early-stage hormone-sensitive breast cancer. Patients completed a self-administered questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…In a substudy of the BIG 1-98 international trial, letrozole-treated patients with the C allele at rs2077647 had a 25% lower risk of bone adverse events (HR=0.75 (0.58-0.98)), whereas patients with the A allele at the ESR2 3'-UTR polymorphism rs4986938 had a 37% greater risk compared with those with wild-type genotype (HR=1.37 (1.01-1.84)) [91]. However, unlike the aforementioned study in Chinese patients [86], no association was found of ESR1 rs2234693 and rs9340799 genetic variant carriers with bone adverse events in the predominantly European population. These conflicting results may be due to differences in ethnicity (and thus minor allele frequencies) and the unbalanced sample sizes.…”
Section: Esr1/esr2mentioning
confidence: 73%
See 2 more Smart Citations
“…In a substudy of the BIG 1-98 international trial, letrozole-treated patients with the C allele at rs2077647 had a 25% lower risk of bone adverse events (HR=0.75 (0.58-0.98)), whereas patients with the A allele at the ESR2 3'-UTR polymorphism rs4986938 had a 37% greater risk compared with those with wild-type genotype (HR=1.37 (1.01-1.84)) [91]. However, unlike the aforementioned study in Chinese patients [86], no association was found of ESR1 rs2234693 and rs9340799 genetic variant carriers with bone adverse events in the predominantly European population. These conflicting results may be due to differences in ethnicity (and thus minor allele frequencies) and the unbalanced sample sizes.…”
Section: Esr1/esr2mentioning
confidence: 73%
“…Estrogenic effects in bone, include the regulation of bone turnover and maintenance of bone mass, result from binding of estradiol to ESR1 [82][83][84][85]. In a study of 436 postmenopausal women receiving adjuvant anastrozole or letrozole therapy for early stage breast cancer, two ESR1 SNPs have been found to have an impact on the incidence of AI-related MSAEs [86]. The intronic SNP rs2234693 influences enhancer activity levels of ESR1…”
Section: Esr1/esr2mentioning
confidence: 99%
See 1 more Smart Citation
“…Postmenopausal Chinese patients with breast cancer carrying an ESR1 rs2234693 CC genotype or rs9340799 AA genotype had an increased risk of AI-related musculoskeletal AEs [35]. In fact, several studies suggest that the effect of the ESR1 polymorphisms on breast cancer risk is hormone-related and dependent on the woman’s hormonal context, showing statistically significant associations mainly in premenopausal women [23].…”
Section: Discussionmentioning
confidence: 99%
“…Today, this technology is widely used and has become a standard in specific gene mutation detection in large cohorts of patients [88], in pharmacogenomics response prediction of the side effects in chemotherapy in cancer treatment [89,90] and in the discovery of disease susceptibility due to gene mutations [91].…”
Section: Snp Genotyping Using Mass Spectrometrymentioning
confidence: 99%